#### Answer

(a) Position 4
(b) Position 1
(c) Position 2
(d) Position 3

#### Work Step by Step

(a) The graph of $y=(x-1)^2-4$ is the graph of $y=x^2$ shifted 1 unit to the right and 4 units down. Hence the graph in position 4 is the graph of this equation.
(b) The graph of $y=(x-2)^2+2$ is the graph of $y=x^2$ shifted 2 units to the right and 2 units up. Hence the graph in position 1 is the graph of this equation.
(c) The graph of $y=(x+2)^2+2$ is the graph of $y=x^2$ shifted 2 units to the left and 2 units up. Hence the graph in position 2 is the graph of this equation.
(d) The graph of $y=(x+3)^2-2$ is the graph of $y=x^2$ shifted 3 units to the left and 2 units down. Hence the graph in position 3 is the graph of this equation.